Silica-loaded styrene-butadiene rubber in the incorporation of stearamide: The torque properties. Issue 1 (December 2020) - Dhoni, R; Ginting, M; Surya, I
Abstract: This research-study investigated the effects of stearamide on the torque properties of silica-loaded styrene-butadiene rubber (SBR). The SBR was loaded with silica at a settled dose (thirty phr) and the stearamide was mixed into the silica-loaded SBR compounds with varied doses from two to eight phr. The effects of stearamide additions on the maximal torque, minimal torque and torque change of silica-loaded SBR were investigated. It was observed that the stearamide caused some affection in torque properties of the silica-loaded SBR. The stearamide diminished the minimal torque but raised the maximal torque and torque change. The bigger the stearamide doses caused in the lower was the minimal torque but caused in the higher was the torque change. The enhancement in torque was attributed to the role of stearamide as the supplementary plasticizing agent for the silica-loaded SBR compounds. The oily property of stearamide decreased the viscosity and enhanced rubber to filler interaction or crosslinks level, respectively.